INFLUENCE OF PACKAGING DESIGN AND PRODUCT QUALITY ON CUSTOMER SATISFACTION OF JANJI JIWA JILID 656 MALANG CITY - Mikona, Martina Putri; Wijayanti, Rena Feri (SYNTIFIC, 2024)
Background. Product packaging design does hold an important influence in efforts to improve product quality to increase satisfaction with a product. Product quality can motivate purchases by increasing customer satisfaction, quality products will make customers feel satisfied. One of the newcomer brands in the coffee shop business in Malang City. Janji Jiwa Jilid 656 coffee shop is one of the local coffee franchises under PT Lunar Boga. Research Purpose. This study aimed to analyse packaging design and product quality affect customer satisfaction at Janji Jiwa Jilid 656 Malang City. Research Method. This research used quantitative research methods. The collection technique was obtained from a questionnaire. Sampling used non-probality sampling with purposive sampling method with a total sample 100 respondents of Janji Jiwa Jilid 656 Malang City customers. The questionnaire results observed from a Likert scale. Findings. Variables X1 (Packaging Design), X2 (Product Quality), and Y (Customer Satisfaction) are by the value of r-count> from r-table (0.196) and significance <0.05. Packaging design and product quality simultaneously have a significant effect on the satisfaction of Janji Jiwa Jilid 656 Malang City. Conclusion. From the research results, it is hoped that Janji Jiwa Jilid 656 Malang City will ensure and maintain packaging design and product quality and make improvements. So that both aspects are in a stable condition and provide good preferences and can support business continuity and customers will always come back to Janji Jiwa Jilid 656 Malang City and create good customer satisfaction.